Analysis of water content in soap formulation using Fourier Transform Infrared (FTIR) spectroscopy. - Abdul Rohman,; Che Man, Yaakob (INSInet Publications, 2009)
A rapid, sensitive, and non-time consuming method of Fourier Transform Infrared (FTIR) Spectroscopy at wave number of 3600 - 3200 cm-1 has been used for determination of water content in soap samples. The developed method was comparable to AOCS Ca 2c-25 method. A chemometrics partial last square (PLS) was used for constructing a calibration model. The 'leave-one-out" technique was used for cross validation. The correlation between water content using FTIR and AOCS in soap formulation existed a good relationship with coefficient of determination (R2) value of 0.923. This study revealed that FTIR spectroscopy combined with the PLS calibration technique is fast and accurate for quantitative analysis of water content in soap samples.